Probing the ultra-low friction mechanism of hydrogenated carbon films with controllable fullerene-like nano-structures grown with different bias voltage. (November 2022) - Shi, Jing; Zhao, Runqiang; Ke, Shenglan; Wang, Wanrong; Wang, Chengbing
Abstract: Tribological properties of hydrogenated amorphous carbon films (HACFs) are strongly affected by external atmospheres stimulus. This greatly limited its applications in fields that require special trans-atmospheric environments. Here, a unique fullerene-like (FL) nanostructure was designed to embed in amorphous carbon matrix to improve the friction behavior of HACFs in ambient air. High-frequency pulsed plasma-enhanced chemical vapor deposition was employed to deposit the films. The HACFs with fullerene-like (FL) characteristics are fabricated with the 'amorphous to FL' evolutions. At bias voltage of − 950 V, HACF has the highest odd ring fraction (57.3%) and exhibit the lowest coefficient of friction (0.039) and wear rate (2.2 ×10 −8 mm 3 /Nm) in ambient air. This may provide potential strategies for HACFs to expand the tribology application environments. Highlights: Hydrogenated amorphous caron films (HACFs) are prepared with controllable FL clusters embedded in carbon networks. HACFs show high hardness (14.8 GPa), high elastic recovery (76.6%), ultra-low friction behavior (μ = 0.039) in ambient. Pentagonal and heptagonal carbon rings rehybridize into carbon onions, which is stable and oxidation-resistant.